Cost-outcome analysis of joint replacement: evidence from a Spanish public hospital Análisis coste-resultado del remplazo de articulaciones: Evidencia de un hospital público español - José Luis Navarro Espigares; Elisa Hernández Torres (Elsevier, 2008)
Background and objectives: Efficiency-based healthcare decision-making has been widely accepted for some time, with cost per quality-adjusted life year (QALY) as the main outcome measure. Nevertheless, for numerous medical procedures, little data are available on the cost per QALY gained. The aim of the present study was to calculate the cost per QALY gained with primary hip and knee replacement and to compare the result with the cost per QALY for other medical procedures, as well as with the maximum threshold cost considered acceptable in Spain. Methods: We performed a prospective cohort pre-test/post-test study of patients undergoing primary hip or knee arthroplasty. Age, sex, and clinical variables were recorded. Functional status and quality of life were measured by means of the WOMAC and EuroQol instruments, respectively, before the intervention and 6 months later. The direct costs of the intervention were calculated, with length of hospital stay and the prosthesis as the main cost drivers. Results: A total of 80 patients, 40 from each intervention, were included in this study. Both functional and perceived health status improved after the intervention. The number of QALYs gained in the knee cohort was 4.64, while that in the hip cohort was 0.86. The total cost of knee replacement was lower (6,865.52 €) than that of hip replacement (7,891.21 €). The cost per QALY gained was 1,275.84 € and 7,936.12 € for knee and hip interventions, respectively. The calculations performed included a 6% discount rate for health outcomes, a 3% inflation rate for costs, and a success rate of 95% at 15 years. Conclusions: The costs of both knee and hip replacement were lower than the threshold of 30,000 € per QALY considered acceptable in Spain, and compared favorably with other medical and surgical procedures. Fundamento y objetivos: Está ampliamente aceptada la toma de decisiones sanitarias basada en la eficiencia, con el coste por año de vida ajustado por la calidad (AVAC) como medida de resultado. No obstante, aún es escasa la disponibilidad de datos de coste por AVAC de las intervenciones. El objetivo de este trabajo es calcular el coste por AVAC ganado en artroplastia de cadera y rodilla, y compararlo con los costes por AVAC de otras intervenciones, así como con el umbral máximo establecido. Métodos: Estudio de cohortes prospectivo pre-test post-test de pacientes intervenidos de prótesis primaria de cadera o rodilla. Se recogieron variables demográficas, clínicas, funcionales y del estado de salud percibida antes de la intervención y 6 meses después de ésta, mediante los cuestionarios WOMAC y EuroQol, respectivamente. Se calcularon los costes directos de la intervención, considerando la prótesis y la duración de la estancia como determinantes principales del gasto. Resultados: Se incluyeron 80 pacientes, 40 por cada articulación. El estado funcional y la salud autopercibida mejoraron tras la intervención. Se ganaron 4,64 y 0,86 AVAC en intervenciones de rodilla y cadera, respectivamente. El coste por proceso de prótesis de rodilla fue de 6.865,52 € y de cadera de 7.891,21 €. El coste por AVAC ganado es de 1.275,84 € y 7.936,12 € para las intervenciones de rodilla y cadera, respectivamente. Se ha tenido en cuenta una tasa de descuento para los resultados en salud del 6%, una inflación del 3% y una tasa de éxito de las intervenciones del 95% a 15 años. Conclusiones: El coste por AVAC ganado tras artroplastia de rodilla y cadera está dentro del límite considerado aceptable en España (30.000 € por AVAC) y resulta bien posicionado en comparación con otras intervenciones.